2016
DOI: 10.1189/jlb.3a1015-480r
|View full text |Cite
|
Sign up to set email alerts
|

CD63 is tightly associated with intracellular, secretory events chaperoning piecemeal degranulation and compound exocytosis in human eosinophils

Abstract: Eosinophil activation leads to secretion of presynthesized, granule-stored mediators that determine the course of allergic, inflammatory, and immunoregulatory responses. CD63, a member of the transmembrane-4 glycoprotein superfamily (tetraspanins) and present on the limiting membranes of eosinophil-specific (secretory) granules, is considered a potential surface marker for eosinophil degranulation. However, the intracellular secretory trafficking of CD63 in eosinophils and other leukocytes is not understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 38 publications
2
77
0
Order By: Relevance
“…Stimulation with inflammatory stimuli such as CCL11 [5] and tumor necrosis factor alpha (TNF-α) [14] induces increased formation of EoSVs. Moreover, eosinophils naturally activated as observed in hypereosinophilic disorders also exhibit amplified numbers of EoSVs [7].…”
Section: Eosinophil Activation Triggers Formation Of Large Transport mentioning
confidence: 99%
See 4 more Smart Citations
“…Stimulation with inflammatory stimuli such as CCL11 [5] and tumor necrosis factor alpha (TNF-α) [14] induces increased formation of EoSVs. Moreover, eosinophils naturally activated as observed in hypereosinophilic disorders also exhibit amplified numbers of EoSVs [7].…”
Section: Eosinophil Activation Triggers Formation Of Large Transport mentioning
confidence: 99%
“…Ultrastructural studies showed that the increased genesis of EoSVs within these cells is associated with secretion. In eosinophils stimulated with inflammatory stimuli, not only did the total number of EoSVs increase but also did the number of EoSVs in contact with secretory granules undergoing release of their contents [5, 14]. Ultrastructural images obtained by conventional EM applied to human eosinophils have also indicated that EoSV were projecting from granule boundaries.…”
Section: Eosvs Are Formed From Secretory Granulesmentioning
confidence: 99%
See 3 more Smart Citations